2011
DOI: 10.1007/s00383-011-2932-2
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma does not have standard course in children

Abstract: Total thyroidectomy and excision of affected lymph nodes is the current mode of surgical management for thyroid papillary carcinoma in children. However, especially in young children (<10 years), modified lymph node dissection should be added to total thyroidectomy in order to avoid leaving the residual tumor foci which can impair the efficacy of the ablation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
10
0
8
Order By: Relevance
“…12 Past studies concerning US of pediatric thyroid nodules reported rates of microcalcifications in malignant nodules ranging from 25% to 44%, which are much lower than the rates found in our study. 10,16 This discrepancy might be due to variation in histologic types in the study populations or sample size. Additionally, the US resolution and/or definition of what constituted microcalcification may have differed between the studies because the type of US equipment and terminology used were not always explicitly stated.…”
Section: Discussionmentioning
confidence: 99%
“…12 Past studies concerning US of pediatric thyroid nodules reported rates of microcalcifications in malignant nodules ranging from 25% to 44%, which are much lower than the rates found in our study. 10,16 This discrepancy might be due to variation in histologic types in the study populations or sample size. Additionally, the US resolution and/or definition of what constituted microcalcification may have differed between the studies because the type of US equipment and terminology used were not always explicitly stated.…”
Section: Discussionmentioning
confidence: 99%
“…L'hypoparathyroïdie persistante est directement corrélée au nombre de glandes parathyroïdes préservées lors de la chirurgie [6]. Dans les séries pédiatriques, les taux d'hypoparathyroïdie définitive varient de 5,5 % à 25 % [5]. D'après Sugino et al [15], cette complication est aussi fréquente chez l'enfant que chez l'adulte.…”
Section: Discussionunclassified
“…Les indications chirurgicales doivent être posées après discussion entre endocrinologue pédiatrique et chirurgien spécialisé dans la chirurgie thyroïdienne [4]. Le geste en lui même comporte des spécificités en termes de réalisation technique et de complications postopératoires [5,6].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Although still controversial, evidence suggests an increased risk of papillary thyroid carcinoma in patients with Hashimoto's thyroiditis. 46 Given its rarity, however, the ultrasonographic findings of papillary thyroid carcinomas that arise from Hashimoto's thyroiditis in the pediatric and adolescent population are not well known. Here, we report the ultrasonographic findings of papillary thyroid cancer with underlying adolescent Hashimoto's thyroiditis.…”
Section: Introductionmentioning
confidence: 99%